The status of industrialization and development of exosomes as a drug delivery system: A review - Yin, Yi; Han, Xing; Li, Cheng; Sun, Tonghui; Li, Kailin; Liu, Xionghao; Liu, Mujun (Frontiers in Pharmacology, 2022)
As a natural biological macromolecule carrier produced by cells, exosomes have the potential and advantages to deliver drugs to target organs or cells in vivo. The improvement steps of exosomes as a drug delivery system can be divided into three steps: mass preparation of exosomes, loading of drugs, and targeted delivery of exosomes. Based on the existing production process and technology, there is still much room for improvement. The possibility of the clinical application of exosomes as an efficient delivery system should be explored. This article major focuses on the research progress in three aspects of exosomes-preparation, loading efficiency, and targeting. Moreover, this article will review new technologies and innovative methods to improve the efficiency of exosome delivery.